ANALISIS BIOMEKANIKA TEKNIK TENDANGAN PENALTI PADA PERMAINAN FUTSAL: STUDI KASUS SMA NEGERI 1 LOA JANAN - Batara Family, Azdam Mangku Batara; Julianur (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This study was motivated by the essential role of penalty-kick technique in futsal, particularly among high school students who are still developing fundamental motor skills. Penalty kicks frequently determine match outcomes and require precise control of movement. This research aimed to describe the biomechanical characteristics of penalty-kick performance among students at SMA Negeri 1 Loa Janan by examining the support-leg angle, swing-leg angle, and movement patterns across the preparation, contact, and follow-through phases. A quantitative descriptive design was employed involving two subjects selected based on their basic futsal skills. Data were collected through video recordings and analyzed using Kinovea software to obtain quantitative measurements of joint angles. The results indicate that Subject 1 demonstrated more consistent angular patterns across all phases, particularly in support-leg stability and body orientation at ball contact (mean support-leg angles: 139–169°). Subject 2 showed a larger swing-leg amplitude but less stable body control, resulting in greater angular variability between phases (range: 130–179°). These inconsistencies reduced the efficiency of force transfer and directional control during the kick. Overall, the findings confirm that biomechanical analysis provides an objective basis for evaluating and improving penalty-kick technique in school-level futsal training. The integration of motion-analysis technology is recommended to assist coaches in identifying technical errors more accurately, thereby enhancing training effectiveness, safety, and adherence to biomechanical principles.